2019
DOI: 10.1038/s41533-019-0127-9
|View full text |Cite
|
Sign up to set email alerts
|

Age- and sex-specific prevalence of chronic comorbidity in adult patients with asthma: A real-life study

Abstract: The presence of comorbidity can be associated with poorer asthma outcomes. Previous prevalence studies focused on a limited selection of comorbid conditions in asthma only. We aimed to determine age- and sex-specific prevalence estimates for the full range of chronic comorbid conditions in adult asthma patients by performing a retrospective cohort study based on 32,787 medical records of patients aged ≥16 years with asthma from 179 general practices in the Netherlands. Age- and sex-specific prevalence estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…The higher proportion of female patients and the different prevalence of certain comorbidities are both well-documented aspects of asthmatic populations [ 4 , 20 23 ]. Veenendaal et al [ 20 ] examined the prevalence of comorbidities of more than 32,000 asthmatic patients and showed that females are affected by overall comorbidities at a higher rate compared with males, with significant differences in certain disease categories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher proportion of female patients and the different prevalence of certain comorbidities are both well-documented aspects of asthmatic populations [ 4 , 20 23 ]. Veenendaal et al [ 20 ] examined the prevalence of comorbidities of more than 32,000 asthmatic patients and showed that females are affected by overall comorbidities at a higher rate compared with males, with significant differences in certain disease categories.…”
Section: Discussionmentioning
confidence: 99%
“…The higher proportion of female patients and the different prevalence of certain comorbidities are both well-documented aspects of asthmatic populations [ 4 , 20 23 ]. Veenendaal et al [ 20 ] examined the prevalence of comorbidities of more than 32,000 asthmatic patients and showed that females are affected by overall comorbidities at a higher rate compared with males, with significant differences in certain disease categories. Other studies have also presented a significant gender-related difference in certain comorbidities, including hypertension, cardiovascular diseases, depression, osteoporosis, and allergic diseases [ 21 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that one of the most important factors of repeated exacerbations are mental disorders [8]. The most common psychiatric disorders observed in patients with asthma are mood disorders, depression, anxiety disorders and alcohol abuse [9,10]. Due to the frequent coexistence with asthma of psychiatric disorders, it is difficult to conclude whether asthma may increase the probability of psychiatric disorders or mental disorders may lead to asthma exaxerbation [5,11].…”
Section: Bronchial Asthmamentioning
confidence: 99%
“…However, according to Braido et al [3], up to 56% of patients do not have a proper level of disease control. One of the significant obstacles to achieving BA control is the presence of comorbid conditions [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, according to Braido et al [ 3 ], up to 56% of patients do not have a proper level of disease control. One of the significant obstacles to achieving BA control is the presence of comorbid conditions [ 4 8 ]. In the list of common variants of comorbidity in recent years, close attention is focused on the combination of BA and obesity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%